Encouraging Knowledge Sharing Behavior to Boost the Business Performance of Creative Industry (Study in Indonesia SMES’s Context) - Ariani Wulansari, N; Ranihusna, D; ., Palupiningdyah (KnE Social Sciences, 2018)
SMEs creative sector has an important and strategic role in national economic development. MSMEs for the Indonesian economy are able to absorb labor about 97% and contribute to gross domestic product (GDP) about 57%. In fact, owners of creative SMEs in the city of Semarang not yet have an awareness of the importance of innovation and creativity development [16]. One of the biggest obstacles is that they do not have a structured program to explore the attractiveness and uniqueness of its products, consequently its products cannot compete competitively with foreign products that increase in the domestic market. The purpose of this study is to examine the factors that can explain the strategy to boost the performance of creative SMEs business through a habit of cultivating the behavior of knowledge sharing between owners, employees, consumers, competitors, government or other stakeholders. The higher the desire to share knowledge then potentially will increasingly bring up innovative ideas that can encourage business performance. The sample consisted of 185 owners of creative SMEs in Semarang City who answered the structured questionnaire. The data is processed by Wrap PLS version 6. The result of the research shows the support of previous research result that UMKM business performance will only be achieved if UMKM actors cultivate knowledge sharing behavior to encourage the emergence of more innovative ideas.